2002
DOI: 10.1128/jcm.40.5.1621-1625.2002
|View full text |Cite
|
Sign up to set email alerts
|

18S Ribosomal DNA Typing and Tracking of Acanthamoeba Species Isolates from Corneal Scrape Specimens, Contact Lenses, Lens Cases, and Home Water Supplies of Acanthamoeba Keratitis Patients in Hong Kong

Abstract: We examined partial 18S ribosomal DNA (Rns) sequences of Acanthamoeba isolates cultured in a study of microbial keratitis in Hong Kong. Sequence differences were sufficient to distinguish closely related strains and were used to examine links between strains obtained from corneal scrape specimens, contact lenses, lens cases, lens case solutions, and home water-supply faucets of patients with Acanthamoeba. We also looked for evidence of mixed infections. Identification of Acanthamoeba Rns genotypes was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
183
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(196 citation statements)
references
References 6 publications
(15 reference statements)
10
183
2
1
Order By: Relevance
“…Therefore the methods for their identification in clinical and environmental samples are being developed in order to enable quick and exact detection of amoebae in various environments including the possibility to determine their pathogenicity. Several studies have reported the presence of Acanthamoeba in the environment (Červa 1971;Booton et al 2002;Ettinger et al 2003;Kilvington et al 2004;Tsvetkova et al 2004;Lorenzo-Morales et al 2006;Rezaeian et al 2008). This study confirms Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the methods for their identification in clinical and environmental samples are being developed in order to enable quick and exact detection of amoebae in various environments including the possibility to determine their pathogenicity. Several studies have reported the presence of Acanthamoeba in the environment (Červa 1971;Booton et al 2002;Ettinger et al 2003;Kilvington et al 2004;Tsvetkova et al 2004;Lorenzo-Morales et al 2006;Rezaeian et al 2008). This study confirms Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of this genotype was proven by the works of several authors (Schroeder et al 2001;Walochnik et al 2000b;Booton et al 2002Booton et al , 2005De Jonckheere 2003;Ledee et al 2003). The dominant genotype in GAE and other non-AK infections is T4 followed by T1, T10, T12 (Booton et al 2005), T5 (Barete et al 2007) and T2 (Walochnik et al 2008).…”
mentioning
confidence: 96%
“…The high proportion of Rns genotype T4 strains has been described as the main factor responsible for Acanthamoeba keratitis infections in many countries, i.e. in France (8/11, plus additional recent data) [24,25], in Greece (4/5) [12], in Hong Kong (12/13) [26], and in the UK and Iran (17/24) [8], thus providing further support to the evidence that the T4 genotype plays a prominent role in the epidemiology of AK human infections.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches that have been useful include RFLP analysis of the entire mitochondrial genome, 12,20-25 riboprinting (described below) of 18S rDNA, 12,26 production of typespecific PCR amplimers, [27][28][29][30] analyses based on sequences of subgenic PCR amplimers [30][31][32] as well as the development of fluorescent oligonucleotide probes for in situ staining that are specific either for the genus Acanthamoeba or for genotype T4. 33 The recent introduction of a 'reverse dot-blot' technique holds promise for the eventual simultaneous detection and identification of all rDNA genotypes present in any specimen.…”
Section: Molecular Epidemiologymentioning
confidence: 99%